Examination of Helicobacter pylori DNA in tap waters and bottled drinking waters (Annals of Medical Research, 2021)
Aim: Helicobacter pylori is bacterium which colonizes the human gastric mucosa and known to affect half of the world’s population. H. pylori is defined as the aetiological agent of peptic ulcer, gastric adenocarcinoma, and mucosa-associated lymphoid tissue lymphoma. It has been suggested that the transmission of bacterium occurs via fecal-oral, oral-oral, and gastro-oral routes. In the present study, we aimed to investigate the presence of H. pylori DNA in drinking and tap water samples.Materials and Methods: Sixty-six different trademarked drinking and 36 different tap water samples were collected from March 2019 - February 2020 all around Turkey. All water samples were filtrated using 0.22 µM membrane filters and filters were incubated in Brain Heart Infusion Broth for a half-hour at room temperature. Then, bacterial DNA was extracted. To detect H. pylori DNA, ureC (glmM) gene was investigated by Polymerase Chain Reaction (PCR). The PCR products were visualized in 1.5 % agarose gel electrophoresis.Results: In this study, H. pylori DNA was not detected in any of the water samples tested.Conclusion: In the present study, it was suggested that drinking and tap waters do not have a role in the transmission of H. pylori in this geographical area. Investigation of 500 mL of bottled waters could be one of the most obvious limitations in this study. Therefore it may be concluded that different water sources such as 19L flagon bottled drinking waters, water samples from various tanks, well waters, groundwater, and surface waters from rivers, lakes, or seas may be useful for clarifying the role of water for transmission route of this pathogen.